DEVELOPMENT OF “AVATAR” LEARNING MEDIA USING SMART APPS CREATOR (SAC) TO IMPROVE STUDENT ABSTRACTION ABILITY - Kurnia Sekarsari; Swasti Maharani; Reza Kusuma Setyansah (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research is motivated by the low ability of students' abstraction while abstraction ability is a very important ability possessed by students. Based on the results of observations and interviews with one of the mathematics teachers at SMPN 1 Jiwan, it was found that students were not able to apply appropriate concepts when working on mathematical problems. In addition, the learning process carried out at SMPN 1 Jiwan still uses conventional methods with the lecture method assisted by print media. This causes a lack of enthusiasm of students when participating in learning. This study aims to develop AVATAR learning media with the Auditory Intellectually Repetition learning model which includes videos, material, sample questions, and practice questions adapted to indicators of abstraction ability and presented interactively so as to improve students' abstraction abilities. This study uses the Research and Development (R&D) method using the 4D development model which consists of the defining stage, the design stage, the development stage, and the deployment stage. The results obtained from this study were that the AVATAR learning media was declared valid with a percentage of 85.00% and very practical with a percentage of 86.36% based on the student response questionnairePenelitian ini dilatarbelakangi oleh rendahnya kemampuan abstraksi peserta didik sedangkan kemampuan abstraksi merupakan kemampuan yang sangat penting dimiliki oleh peserta didik. Berdasarkan hasil observasi dan wawancara dengan salah satu guru matematika di SMPN 1 Jiwan diperoleh hasil bahwa peserta didik belum mampu mengaplikasikan konsep yang sesuai pada saat mengerjakan permasalahan matematika. Selain itu, proses pembelajaran yang dilaksanakan di SMPN 1 Jiwan masih menggunakan cara konvensional dengan metode ceramah berbantuan media cetak. Hal ini menyebabkan kurangnya antusias peserta didik pada saat mengikuti pembelajaran. Penelitian ini bertujuan untuk mengembangkan media pembelajaran AVATAR dengan model pembelajaran Auditory Intellectually Repetition yang di dalamnya memuat video, materi, contoh soal, dan soal latihan yang disesuaikan dengan indikator kemampuan abstraksi serta disajikan secara interaktif sehingga dapat meningkatkan kemampuan abstraksi peserta didik. Penelitian ini menggunakan metode Research and Development (R&D) dengan penggunaan model pengembangan 4D yang terdiri atas tahap pendefinisian, tahap perancangan, tahap pengembangan, dan tahap penyebaran. Hasil yang diperoleh dari penelitian ini yaitu media pembelajaran AVATAR dinyatakan valid dengan hasil persentase 85,00% serta dinyatakan sangat praktis dengan persentase 86,36% berdasarkan angket respon peserta didik.